2018
DOI: 10.1242/jcs.212191
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 proteins regulate desmosomal adhesion via plakophilins

Abstract: Desmosomes are essential for strong intercellular adhesion and are abundant in tissues exposed to mechanical strain. At the same time, desmosomes need to be dynamic to allow for remodeling of epithelia during differentiation or wound healing. Phosphorylation of desmosomal plaque proteins appears to be essential for desmosome dynamics. However, the mechanisms of how context-dependent post-translational modifications regulate desmosome formation, dynamics or stability are incompletely understood. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…Importantly, our findings have identified that Dsg3 serves as an upstream regulator of YAP/pYAP and forms a complex with and sequesters pYAP to the plasma membrane, a process that involves PKPs, to facilitate AJ assembly ( Figure 10). A recent report has identified that the desmosomal plaque proteins PKP1/3 bind to 14-3-3γ/σ isoforms that are required in desmosome adhesion [45]. Another independent study has shown that PKPs interact directly with the cytoplasmic tail of Dsg1-3 [46].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our findings have identified that Dsg3 serves as an upstream regulator of YAP/pYAP and forms a complex with and sequesters pYAP to the plasma membrane, a process that involves PKPs, to facilitate AJ assembly ( Figure 10). A recent report has identified that the desmosomal plaque proteins PKP1/3 bind to 14-3-3γ/σ isoforms that are required in desmosome adhesion [45]. Another independent study has shown that PKPs interact directly with the cytoplasmic tail of Dsg1-3 [46].…”
Section: Discussionmentioning
confidence: 99%
“…10). A recent report has identified that the desmosomal plaque proteins PKP1/3 bind to 14-3-3γ/σ isoforms that are required in desmosome adhesion [42]. Another independent study has shown that PKPs interact directly with the cytoplasmic tail of Dsg1-3 [4].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also detected desmoplakin (DP), junction plakoglobin, plakophilin‐1, and envoplakin on the volar forearm skin of the volunteers. DP is an obligate component of desmosomes and is essential for strong intercellular adhesion . In the epidermis, the adhesive strength of desmosomes is controlled by plakophilin (PKP) isoform expression, which facilitates the tissue remodeling that is required during regeneration and wound healing .…”
Section: Discussionmentioning
confidence: 99%
“…36 In the epidermis, the adhesive strength of desmosomes is controlled by plakophilin (PKP) isoform expression, which facilitates the tissue remodeling that is required during regeneration and wound healing. 36 Envoplakin plays a role in cell-to-cell adhesion, and the plakin repeat domain (PRD) of envoplakin is the key to direct attachment of membranes to the cytoskeleton. 37 Corneodesmolysis is also usually associated with CE maturation and ultimately desquamation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation